The Influence of Visual Learning Style and Self-Efficacy Towards Students' Reading Comprehension - Virdaus, Varia Virdania; Rifa’i, Saiful (Journal of Development Research, 2025)
In the context of senior high school education, this study examines the relative contributions of visual learning style and self-efficacy on students' reading comprehension. 120 eleventh-grade students were chosen for the study using stratified random sampling, which was framed inside a quantitative correlational research design. A standardized reading comprehension exam, a self-efficacy scale, and a validated visual learning style questionnaire were among the tools used to collect the data.Self-efficacy emerged as the stronger predictor, however both visual learning style and self-efficacy had a statistically significant impact on reading comprehension, according to multiple regression analysis. These results highlight how crucial it is to support kids' self-belief and cater to their unique learning styles in order to improve reading performance. With a focus on the incorporation of visually enhanced instructional tactics and self-efficacy-enhancing interventions into English language teaching practices, the study provides pedagogical implications for educators and curriculum developers.